Quality Seed Accessibility Index: A Case Study from a Village in Western Rajasthan - B. L. Manjunatha , Dipika Hajong , Pratibha Tewari , Bhagwan Singh , C. S. Shantaraja , Prashant H Nikumbhe , N. K. Jat , K. Shiran; R. P. Parihar (Indian Journal of Extension Education, 2018)
The availability of quality seeds for sowing is a critical factor affecting crop production. A Seed Accessibility Index was developed to assess the extent of accessibility of quality seeds by farmers from formal and informal sources. The study was undertaken in Jodhpur district in western Rajasthan involving a sample of farm households (60), representatives from Rajasthan State Department of Agriculture (2), Rajasthan State Seeds Corporation (RSSC) (1), Rajasthan State Seed and Organic Production Certification Agency (1), National Seeds Corporation (1), private seed dealers (5) and private seed companies (PSCs) (5). Accessibility Index (AI) was found to be highest (86.67%) for farm saved seeds (carrot, onion and garlic) indicating that the seeds/planting material in these crops were easily and timely available, affordable, credible and performed as expected without any cases of spurious seeds. In case of seeds purchased from market, timely availability was not an issue but the seeds of desired variety were not always available. The probability of crop failure on account of spurious seeds was found to be higher in those crops for which farmers were completely dependent on market. PSCs and dealers’ agreed that probability of cases of spurious seeds was 2-3 per cent. However, the economic loss caused to those farmers who suffered crop loss because of spurious seeds is huge. Price of seeds purchased from market was found to have less AI (62.33) indicating that seeds are no more a cheaper input in agriculture. The farmers’ practice of higher seed rate than recommended, resowing for 2-3 times and complete dependence on market have led to increased expenditure on seed. The study indicated that the role and importance of informal seed sector (as in carrot) has been grossly underestimated or even overlooked by researchers and policymakers. On the other hand, the role of formal sector (especially PSCs) is overestimated and even glorified. It is also evident that high Seed Replacement Rate (SRR) in itself doesn’t guarantee quality of seed and crop performance.